2018
DOI: 10.3168/jds.2017-14288
|View full text |Cite
|
Sign up to set email alerts
|

Measuring labor input on pasture-based dairy farms using a smartphone

Abstract: With the cessation of milk quotas in the European Union, dairy herd sizes increased in some countries, including Ireland, with an associated increase in labor requirement. Second to feed costs, labor has been identified as one of the highest costs on pasture-based dairy farms. Compared with other European Union countries, Ireland has historically had low milk production per labor unit; thus, optimization of labor efficiency on farm should be addressed before or concurrently with herd expansion. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 20 publications
5
99
0
1
Order By: Relevance
“…; Deming et al . ) and the increased demand for employed labour when herd size increases (Stahl et al . ).…”
Section: Changes In the Structure Of Irish Dairy Farmsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Deming et al . ) and the increased demand for employed labour when herd size increases (Stahl et al . ).…”
Section: Changes In the Structure Of Irish Dairy Farmsmentioning
confidence: 99%
“…The 2013 CSO Farm Structure Survey highlighted that a large amount of family labour existed on dairy farms (approximately 18 000 family members contributing on average 0.5 annual work units -900 h (CSO Farm Structure Survey 2013). However, numerous studies have shown disparities between the availability of family labour and labour requirement on large-scale dairy farms (Errington and Gasson 1996;O'Brien et al 2007;Deming et al 2018) and the increased demand for employed labour when herd size increases (Stahl et al 1999). Between 2013 and 2016, the CSO Farm Structural Survey indicates that the availability of family labour on dairy farms has reduced at a time when herd size increased dramatically (CSO Farm Structure Survey 2016).…”
Section: Changes In the Structure Of Irish Dairy Farmsmentioning
confidence: 99%
“…The duration of milking is an important consideration in dairy farming for both conventional and automatic milking systems (AMS). In conventional milking systems, the need to minimize production costs and the difficulties of finding skilled labor make the milking process a challenging activity (Jago et al, 2010), especially because milking is the most labor-intensive task on dairy farms, accounting for 33% of overall labor demand (Deming et al, 2018). In AMS, key factors driving efficiency and productivity are milking duration and total time spent milking per day in the robot (Gygax et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Over all this type of system results in more machinery, more time feeding and overall less efficient systems across all of the definitions of efficiency. Financial performance declines [45][46][47], labour efficiency declines [48] and environmental efficiency declines [49,50]. While it could be argued that at high milk price [51] the higher input systems can be competitive on a unit of land basis, in general they will be substantially less profitable per unit of milk output.…”
Section: Farm Fragmentation and Scalementioning
confidence: 99%